2019
DOI: 10.1186/s12967-019-1918-z
|View full text |Cite
|
Sign up to set email alerts
|

Computational models for the prediction of adverse cardiovascular drug reactions

Abstract: Background Predicting adverse drug reactions (ADRs) has become very important owing to the huge global health burden and failure of drugs. This indicates a need for prior prediction of probable ADRs in preclinical stages which can improve drug failures and reduce the time and cost of development thus providing efficient and safer therapeutic options for patients. Though several approaches have been put forward for in silico ADR prediction, there is still room for improvement. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…Adverse effects of drugs, especially organ toxicity, are the main reasons for drug development failure and withdrawal after marketing ( Jamal et al, 2019 ). The current general cell screening and animal model screening often cannot accurately predict adverse reactions in the human body.…”
Section: Application Of Organoids In Crc Researchmentioning
confidence: 99%
“…Adverse effects of drugs, especially organ toxicity, are the main reasons for drug development failure and withdrawal after marketing ( Jamal et al, 2019 ). The current general cell screening and animal model screening often cannot accurately predict adverse reactions in the human body.…”
Section: Application Of Organoids In Crc Researchmentioning
confidence: 99%
“…One of the most difficult steps in the process of drug development is the prediction of adverse effects. It has been reported that computational modeling using machine learning is useful for predicting adverse effects (65). Moreover, it is possible to manufacture synthetic patients and data artificially by analyzing existing data using machine learning techniques (66,67).…”
Section: Ai In Drug Development As a Foundation For Drug Therapymentioning
confidence: 99%
“…However, DPA ignores the influence of a confounding bias in the analysis, which may lead to false positives and an under-detection of ADEs ( DuMouchel, et al, 2013 ; Candore, et al, 2015 ). To overcome these limitations, machine learning algorithms and other methods have been used to detect ADEs using SRSs; some network-based methods and machine learning algorithms have been developed to predict ADEs using different public databases ( Cami, et al, 2011 ; Liu, et al, 2012 ; Cheng, et al, 2013 ; Lin, et al, 2013 ; Davazdahemami and Delen, 2018 ; Jamal, et al, 2019 ). For example, a pharmacological network model (PNM) was developed to predict new and unknown drug-ADE associations ( Cami, et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al integrated the phenotypic characteristics of drugs (i.e., indications and known adverse drug reactions), chemical structures, and biological properties of protein targets and pathway information, and used five machine learning methods to predict ADEs ( Liu, et al, 2012 ). Moreover, Jamal et al integrated the biological, chemical, and phenotypic features of drugs and used machine learning methods (random forest and sequential minimum optimization) to predict cardiovascular adverse reactions ( Jamal, et al, 2019 ). Their results showed that the phenotypic data showed the best prediction effect and that drugs with similar chemical structures were more likely to exhibit similar ADEs.…”
Section: Introductionmentioning
confidence: 99%